2023
DOI: 10.1002/asia.202300773
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling the Effect of Acid‐Driven Electron Transfer in High‐Valent FeIV=O/MnIV=O Species and Its Implications for Reactivity

Neethinathan Johnee Britto,
Asmita Sen,
Gopalan Rajaraman

Abstract: Metalloenzymes with metal‐oxo units usually involve outer‐sphere electron transfer (OSET). In contrast, biomimetic models exhibit inner‐sphere electron transfer (ISET) or OSET. This is evident in complexes [(N4Py)MnIV(O)]2+ (1) and [(N4Py)FeIV(O)]2+ (2) in the presence of Lewis/Bronsted acid with 1 showcases an OSET mechanism, while 2 exhibits an ISET mechanism. However, the precise reason for this puzzling difference remains elusive.This work unveils the origin of the perplexing inner‐sphere vs outer‐sphere e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 61 publications
0
1
0
Order By: Relevance
“…Employing a slightly higher basis set (LANL2TZ for Fe and 6-311G** for H, C, O, and N) yields similar spin-state ordering, with the gap found to vary marginally for 1 (within 4 kJ/mol). The functional was chosen based on the earlier literature and benchmarking available on similar systems and the ability of B3LYP functional to interpret a correct ground state for the Fe IV O species. , A comprehensive benchmark investigation conducted by de Visser and colleagues, focusing on the non-heme Fe IV O-catalyzed sulfoxidation of thioanisole utilizing diverse DFT functionals (B3LYP, BP86, and PBE0) and basis sets revealed the superior ability of the B3LYP functional to accurately replicate both the experimental trends and absolute values of the free energy of activation . Our group has also investigated a series of oxidative transformations employing various heme/non-heme ferryl–oxo complexes and explored a spectrum of density functionals, including B3LYP, B97-D, ωB97X-D, and M06-2X. Our analysis revealed that the B3LYP and ωB97X-D functionals consistently produce accurate ground states for all of the species examined.…”
Section: Computational Detailsmentioning
confidence: 99%
“…Employing a slightly higher basis set (LANL2TZ for Fe and 6-311G** for H, C, O, and N) yields similar spin-state ordering, with the gap found to vary marginally for 1 (within 4 kJ/mol). The functional was chosen based on the earlier literature and benchmarking available on similar systems and the ability of B3LYP functional to interpret a correct ground state for the Fe IV O species. , A comprehensive benchmark investigation conducted by de Visser and colleagues, focusing on the non-heme Fe IV O-catalyzed sulfoxidation of thioanisole utilizing diverse DFT functionals (B3LYP, BP86, and PBE0) and basis sets revealed the superior ability of the B3LYP functional to accurately replicate both the experimental trends and absolute values of the free energy of activation . Our group has also investigated a series of oxidative transformations employing various heme/non-heme ferryl–oxo complexes and explored a spectrum of density functionals, including B3LYP, B97-D, ωB97X-D, and M06-2X. Our analysis revealed that the B3LYP and ωB97X-D functionals consistently produce accurate ground states for all of the species examined.…”
Section: Computational Detailsmentioning
confidence: 99%